Perioperative Provider and Staff Competency in Providing Culturally Competent LGBTQ Healthcare in Pediatric Setting [Corrigendum] - Walia H; Banoub R; Cambier GS; Rice J; Tumin D; Tobias JD; Raman VT (Advances in Medical Education and Practice, 2020)
Walia H, Banoub R, Cambier GS, et al. Adv Med Educ Pract. 2019;10:1097–1102.The authors advised that there should be an added acknowledgment section. The authors apologize for this error.Read the original article